Attitudes, beliefs, and practices regarding complementary and alternative medicine use: Influenza vaccine intake. - Dala N Daraghmeh; Ahmad Salah; Nasim Hamdan; Abdallah Zamareh (PLoS ONE)
Objectives Influenza poses a major health challenge due to its variability and pandemic potential, making prevention crucial. The study aimed to explore the link between influenza vaccination and complementary and alternative medicine (CAM) practices among Palestinian adults, along with factors influencing vaccination rates. It also evaluated participants' attitudes towards CAM and beliefs regarding herbal and vitamin use for influenza management. Methods A cross-sectional study was carried out between 18/02/2024 and 23/04/2024, during which a self-administered online questionnaire was shared through social media and personal communication. This questionnaire was aimed at all adults aged 18 and above. Both descriptive and regression analyses were performed. Results The study included 363 participants, revealing an influenza vaccination rate of only 9%. A significant correlation was found between manipulative, body-based methods, mind-body medicine, and vaccination status (P-value<0.05), while no significant relationship was noted with herbal remedies or alternative medical systems. Higher income and better health status were linked to increased vaccination likelihood (P-value<0.05), indicating a need for targeted public health campaigns. Although 63% of participants were familiar with complementary and alternative medicine (CAM), 34% had never used it for influenza, highlighting a knowledge gap. Popular natural remedies like Vitamin C, ginger, and honey reflect a trend toward preventive healthcare despite concerns over costs and skepticism about CAM's effectiveness. Conclusion Vaccine hesitancy is influenced by multiple factors, including context and types of CAM use. Cultural beliefs and personal health philosophies significantly shape attitudes toward CAM use and vaccination.